Tuberculosis Sanatorium of 21st Century Exploring the Admission Pattern and Duration of Stay at TB Sanatorium Bhowali, Uttarakhand, India: A Retrospective Study - Debnath, Aninda; Chandra, Ankit; Maroof, Mohd.; Awasthi, Sadhana; Arya, Monika (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
Introduction: With time there have been major changes in the management of TB. No longer TB sanatoriums are preferred. However, in this 21st century, few sanatoriums do exist but are no longer in their original forms, to explore the admission patterns and duration of stay at the TB sanatorium Bhowali, Uttarakhand. Methodology: We retrieved the data between 1st January 2018 to 31st July 2021 from the inpatient Department (IPD) of TB sanatorium Bhowali. Data were extracted in an extraction sheet and descriptive data analysis was done to see the admission patterns and duration of stay. The place of residence was analysed as per the district-wise distribution. Results: There were 1247 admissions. These admissions were limited to six states, and the majority were from the state of Uttar Pradesh (50.7%) and Uttarakhand (46.7%). The highest cases were in the year 2018, and during April to July. As per the district-wise distribution, Udham Singh Nagar had the highest proportion of admissions (18.6%), followed by Bareilly (15%), Nainital (11.4%), and Rampur (10.9%). The mean (SD) and median (IQR) duration of stay were 22.7 days (SD–24.7) and 14 (IQR 7– 8) days, respectively. The median duration of stay was significantly higher for females (25.1 days) compared to males (21.6 days). Conclusion: TB sanatorium Bhowali (Uttarakhand) caters majority of the patients from the neighbouring state of Uttar Pradesh. The admissions were high during the spring and summer seasons. The median duration of hospital stay for patients admitted with TB was two weeks.